2020
DOI: 10.1186/s12903-020-01273-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and practice of dentists towards Coronavirus Disease (COVID-19): a cross-sectional survey from Lebanon

Abstract: Background Coronavirus Disease (COVID-19) epidemic is a public health emergency of international concern. Dentists are exposed to the enormous risk of COVID-19 infection during this epidemic. This study aims to assess the knowledge and practice of dentists toward the COVID-19 epidemic in Lebanon. Methods We conducted an online survey using the snowball-sampling technique. Information on socio-demographic data, knowledge, practice, and additional information required concerning COVID-19 were collected. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 20 publications
17
47
1
Order By: Relevance
“…The resulting insights allow a deep understanding of barriers and enablers to implementation both on an emotional but also a factual level. Notably, our findings can be triangulated with those of quantitative evaluations (e.g., from surveys), which highlighted that knowledge on COVID-19 increased with time and was generally not the main barrier for ICM in more recent surveys; that the adoption of PPE varied widely and that some PPE, such as face shields and FFP2-masks, were not implemented regularly; that there was uncertainty regarding how to adapt practice infrastructure and organization to reduce infection risks and that, generally, the specific setting was associated with the implementation of measures [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Our study now adds insights as to why all these observations were made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting insights allow a deep understanding of barriers and enablers to implementation both on an emotional but also a factual level. Notably, our findings can be triangulated with those of quantitative evaluations (e.g., from surveys), which highlighted that knowledge on COVID-19 increased with time and was generally not the main barrier for ICM in more recent surveys; that the adoption of PPE varied widely and that some PPE, such as face shields and FFP2-masks, were not implemented regularly; that there was uncertainty regarding how to adapt practice infrastructure and organization to reduce infection risks and that, generally, the specific setting was associated with the implementation of measures [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Our study now adds insights as to why all these observations were made.…”
Section: Discussionmentioning
confidence: 99%
“…While the knowledge on COVID-19 has increased over the course of the pandemic, the majority of dentists have not yet implemented all recommended measures. A few dentists aimed to exceed recommendations or legal minimum standards [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. It is, however, not clear why implementation differs between measures, dentists and settings.…”
Section: Introductionmentioning
confidence: 99%
“…In Lebanon, there is a lack of data concerning the number of cleaning staff infected by COVID-19 among hospitals but according to the epidemiological surveillance unit data, no deaths were reported among this category. Although those previous studies have evaluated the knowledge and practices of different health care workers toward COVID-19 including physicians (9), dentists (10), pharmacists (11) and nurses (12) no studies have focused on the practices of hospital services staff members, particularly housekeepers.…”
Section: Introductionmentioning
confidence: 99%
“…Our multivariate logistic regression model showed that better knowledge was associated with having high prevention measures index. To our knowledge, only two previous studies explored the factors associated with prevention practices of dental professionals and reported similar association with knowledge [ 19 , 23 ]. Unlike the previous study in Lebanon [ 23 ], the present study showed that specialists dentists were less likely to achieve high prevention measures index compared to general dental practitioners.…”
Section: Discussionmentioning
confidence: 84%
“…To our knowledge, only two previous studies explored the factors associated with prevention practices of dental professionals and reported similar association with knowledge [ 19 , 23 ]. Unlike the previous study in Lebanon [ 23 ], the present study showed that specialists dentists were less likely to achieve high prevention measures index compared to general dental practitioners. We should note that the previous study was based on a snowball sampling technique and might have suffered from lack of representativeness for dental professionals in Lebanon.…”
Section: Discussionmentioning
confidence: 84%